Perancangan Prototype Sistem Informasi Repository Skripsi Berbasis Web Di UNA’IM Yapis Wamena Papua - Syarifah; Chairullah Naury; Wahyuni Nurindah Sulistiyowati (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2022)
In Indonesia, there are many institutions that use information systems in the field of education, one of which is the Repository information system. Repository is a digital-based library term where this information system can be used to access student thesis, both the academic community and academics outside the campus as reference material for writing scientific papers. Even so, not all colleges use it. One of them is Amal Ilmiah Yapis Wamena University. As a university located in conflict and mountainous areas, data loss often occurs. Likewise with the use of information systems that have not been maximized. This study aims to design a prototype of a web-based thesis repository information system at the Amal Ilmiah Yapis Wamena University. The method used is simulated prototyping. The results of this study show the prototype/prototype design in the form of a web-based thesis repository information system mockup as many as 7 (seven) mockup pages, including the login page, lecturer list, Lecturer data entry form, student list, student data entry form, repository list, and form. repository data entry.